LANGUAGE STYLE OF FITZGERALD IN THE GREAT GATSBY - Syukri, Masyitah (Universitas Hasanuddin, 2019)
The aims of this study were to observe (1) the language style often used in textual appearance in literary works, (2) the figures of speech function in mediating the variables to produce the language style of Fitzgerald’s novel. The research was descriptive qualitative approach. The source of the data in this research was the novel The Great Gatsby written by Fitzgerald. The data were collected by using note-taking technique and were analyzed by listing and categorizing figures of speech based on stylistics approach proposed by Geoffrey Leech and Mick Short’s theory. The results of the research indicated that (1) this research has seven categories of figures of speech. The mostly used is simile which has 38 data, metaphor which has 4 data, personification which has 25 data, irony which has 15 data, hyperbole which has 14 data, litotes which has 6 data and the last is synecdoche which has 3 data. In those figures of speech, the researcher found that the author used animals, other living objects, inanimate objects, visible and invisible things to express human feeling, attitude, and characteristic toward something in certain situation and condition so that the readers can understand clearly the objective of the author expression. (2) The use of figures of speech in mediating the variables to produce the language style of Fitzgerald’s novel has function to increase the readers’ taste, to persuade the readers, to increase the artistic effect, to clarify idea, to influence the readers’ feeling and thinking and to emphasize idea of the author.